Digital Literacy of Cisungsang Indigenous Community through Tular Nalar - Yusanto, Yoki; Sjuchro, Dian Wardiana; Nurfauziah, Isni (Jurnal Communio : Jurnal Jurusan Ilmu Komunikasi, 2024)
The digital age requires people, including indigenous peoples, to be aware of the positive and negative impacts of social media. The negative impacts need to be addressed effectively through digital literacy programmes. Tular Nalar comes as a digital literacy programme in the form of informal education. The purpose of this research is to understand the Communication Experience, Motives, and Meanings of Tular Nalar activities in Kasepuhan Cisungsang. This descriptive qualitative research uses a phenomenological approach as its research method. Data were collected through observation and interview techniques. The research findings show that the Tular Nalar programme has a positive meaning for the indigenous people of Kasepuhan Cisungsang. The research also revealed the tendency of indigenous people to share information with others due to the additional knowledge gained at Kasepuhan Cisungsang. Furthermore, the study revealed that digital literacy training not only improves individuals' skills in using technology but also creates a positive domino effect through knowledge sharing and awareness of the dangers of misinformation